Who is open data for and why could it be hard to use it in the digital humanities? Federated application programming interfaces for interdisciplinary research. (2017) - Sugimoto, Go
Open data has prevailed across the research community for the past few years. However, there are a number of reasons why data reuse could be hard for digital humanities scholars. This paper is based on an application that addresses the issues of data-owning culture, interdisciplinary studies, and distributed-data research in terms of Application Programming Interface (API) and open data. The James Cook Dynamic Journal assists users to study the Cook's journal, by aggregating information from various sets of APIs that facilitate full-text search, named entity recognition, and map views. The development of the application revealed some critical issues of data federation and processing automation. In particular, the standardisation of JSON and the development of user-friendly GUI tools would significantly increase the value of APIs. The paper also proposes 'Easy Data' to avoid a digital divide and to liberate open data for a wider spectrum of users.